2013
DOI: 10.1128/iai.00316-13
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Prophylaxis with CpG Oligodeoxynucleotide Can Protect against Yersinia pestis Infection

Abstract: Immunomodulatory agents potentially represent a new class of broad-spectrum antimicrobials. Here, we demonstrate that prophylaxis with immunomodulatory cytosine-phosphate-guanidine (CpG) oligodeoxynucleotide (ODN), a toll-like receptor 9 (TLR9) agonist, confers protection against Yersinia pestis, the etiologic agent of plague. The data establish that intranasal administration of CpG ODN 1 day prior to lethal pulmonary exposure to Y. pestis strain KIM D27 significantly improves survival of C57BL/6 mice and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
10
0
2
Order By: Relevance
“…Furthermore, the same mice prophylactically treated with the ODN resisted MRSA infection. Treatments aimed at restoring the host's immune function have been shown to be effective for preventing the onset of infections in immunocompromised hosts; 24 , 25 , 26 , 27 , 28 , 29 however, the control of MRSA infection using immunologically acting substances remains limited. In our studies, the growth of MRSA was shown to be minimal in the blood and other organs of 25% TBSA burn mice therapeutically treated with the ODN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same mice prophylactically treated with the ODN resisted MRSA infection. Treatments aimed at restoring the host's immune function have been shown to be effective for preventing the onset of infections in immunocompromised hosts; 24 , 25 , 26 , 27 , 28 , 29 however, the control of MRSA infection using immunologically acting substances remains limited. In our studies, the growth of MRSA was shown to be minimal in the blood and other organs of 25% TBSA burn mice therapeutically treated with the ODN.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the T4 phage DNA containing CpG might potentially serve as a T H 1-type of adjuvant. Indeed, studies have shown that F1-V vaccine adjuvanted with CpG or poly IC (also a T H 1 type adjuvant), given by the intranasal route, induced both T H 1 and T H 2 responses, providing better protection to mice against bubonic and pneumonic plague [55], [56]. Thus, T4 might be a particularly useful platform for plague vaccine design since clearance of the Y. pestis bacterium may require a balanced response that is generally not seen with the current F1-V vaccines [46].…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant interest in using cytosine-phosphate-guanine (CpG)-containing oligodeoxynucleotides (ODNs) as an adjuvant for preventative therapeutic measures [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. CpG provides protection from a variety of pathogens, such as Klebsiella pneumoniae, Yersinia pestis, Listeria monocytogenes, Burkholderia pseudomallei , respiratory syncytial virus and human immunodeficiency virus, by enhancing non-specific immunity commonly associated with a strong polarized Th1-cell response, including increased production of IFN-γ and Th1-associated antibody isotypes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Pre- and post-vaccination with CpG has been shown to protect and in some cases may contribute to the cessation of disease transmission [ 20 ].…”
Section: Introductionmentioning
confidence: 99%